Stocktaking of policy, institutional readiness, and carbon initiatives for Just Low-carbon Transitions in the Philippines, Thailand, and Vietnam - Batin, Cynthia Jean; Gonzalez, Tobiah R.; Pajadan, Karen; Dela Rueda, Justin; Yaowapruek, Boonrod; Almonares, Ray Anthony; Welutung, Phatchariya; Sukpholtham, Sitthichat; Hai, Le Trong; Tran, Nghia Dai; Dinh, Dung Thi Kim; Cuong, Ong Quoc; et al. (International Rice Research Institute, 2025)
This synthesis report consolidates the information on the policy landscape, institutional readiness, and carbon-mitigation initiatives in the Philippines, Thailand, and Vietnam, with a specific focus on accelerating methane reductions in rice systems. It reviews national climate commitments (NDCs), sectoral policies, and regulatory frameworks influencing low-carbon rice cultivation, particularly the adoption of AWD and related climate-smart practices. The report also provides detailed assessments of each country’s carbon market initiatives—including CDM, voluntary carbon market projects, Article 6 readiness, results-based climate finance, and emerging JCM projects—and evaluates institutional capacity for monitoring, reporting, and verification (MRV). Through comparative stakeholder mapping and synthesis tables, the publication identifies gaps, opportunities, and practical entry points for promoting just and inclusive low-carbon transitions across major rice-producing economies in Southeast Asia